Neuroprotective effects of compounds interacting with carrier-mediated amantadine transport across the blood–retinal barrier in rats - Shinozaki, Yusuke; Akanuma, Shin-ichi; Tega, Yuma; Hosoya, Ken-ichi (Journal of pharmacological sciences, 2025)
Retinal drug delivery via peripheral administration enhances the safety and efficacy of retinal pharmacotherapy. As retinal drug distribution from the circulating blood is limited by the blood–retinal barrier (BRB), BRB-permeable retinal drugs with potent pharmacological effects are needed for peripheral administration. Our previous research indicated carrier-mediated retinal transport of amantadine, which has neuroprotective effects by inhibiting N-methyl-d-aspartate receptors, across the BRB. As several amantadine derivatives are also suggestive to strongly interact with the carrier-mediated amantadine transport at the BRB, these compounds are proposed as candidates for the treatment of retinal diseases after peripheral administration. To find the appropriate retinal drug candidate, neuroprotective effects of compounds interacting with carrier-mediated amantadine transport across the BRB were firstly evaluated using primary-cultured rat cortical neurons. As a result, N'-(1-adamantyl)ethane-1,2-diamine (test compound) exerted the most potent neuroprotective effects. In addition, this test compound indicated neuroprotective effects against retinal damage after intraperitoneal administration in retinal damage rats. Our findings suggest the test compound, which interacts with carrier-mediated amantadine transport across the BRB and protected neurons from excitotoxicity in vitro, is a key agent to develop the pharmacotherapy with peripheral administration of medicines for retinal diseases.